Online Healthcare Monitor System Based on Optical Wireless and FBG Sensors - A. Murdas, Ibrahim; N. Jabbar, Ahmed (International Journal of Engineering and Technology, 2018)
In this work, a practical wireless optical communication system has been proposed for the purpose of monitoring the health condition of patients who are in hospital operating on the basis of the wireless communication system and fiber sensors. The suggest practical system employ a diffuse optical broadband link techniqueÂ based on laser Li-Fi the technology, Fiber Bragg grating (FBG) sensors was investigated.Â The focused on optical fiber sensors (pressure and temperature) for medical applications because itâ€™s small size, immunity to electromagnetic interferences and their suitability for remote monitoring. Fiber Bragg grating (FBG) based (blood pressure, temperature) sensors is designed and implemented using a conventional laser source, Optisystem version 15. The collected data from sensors is transmitted to main unit, the suggested system tested under different operating conditions such as , optical link distance, laser power and transmitter angles, all operating conditions was successively demonstrated. Â